(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The study examined the effects of lycopene on markers of liver function and glucokinase activity in experimentally-induced diabetes mellitus rat model. To accomplish this, experimental diabetes were induced by single intra-peritoneal administration of streptozotocin (60 mg/kg b w) into animals. Diabetic and normal animals were randomized into the following groups: Group I: Normal control rats that received (0.5 mL) of olive oil; Group II: Diabetic control animals that received (0.5 mL) of olive oil); while Group III- VI received (10, 20 and 40 mg/kg of lycopene and 2 mg/kg b w glibenclamide) respectively. All treatments were given orally once daily for four weeks. There was a significant (P < 0.05) and progressive reduction on blood glucose concentration, with non- significant (P > 0.05) increase in serum insulin level when compared with diabetic control group. There was a significant (P < 0.05) increase in the activity of liver glucokinase enzyme as well as a significant (P < 0.05) decrease on the activities of serum liver enzymes (AST, ALT and ALP) in diabetic animals administered with lycopene when compared with those of diabetic control animals. Following available evidence from our findings, lycopene may be suggested as a promising dietary agent in the management of diabetes and hepato-cellular damage that usually occurs in diabetes mellitus.